Ear drainage and the role of sepsis evaluations in the neonatal intensive care unit. (11th April 2014) - Khattab, Mona; Cannon‐Heinrich, Charlene; Bizzarro, Matthew J.
Abstract Aim To design and implement an intervention to reduce ear drainage and subsequent sepsis evaluation and treatment in the neonatal intensive care unit. Methods From 2008 to 2011, we observed an increase in the rates of ear drainage warranting investigation. Data collection was performed from 1991 to 2013 on 50 cases. Preliminary analysis revealed an association between timing of endotracheal tube tape changes and onset of drainage. We speculated that pooling of anti‐adhesive solution into the external auditory canal was precipitating an inflammatory process. Unit‐wide education was conducted to protect the ears during tape removal. Post‐initiative rates of drainage were collected and compared with pre‐initiative rates. Results Median gestational age and birthweight were 26 weeks and 754 g, respectively. In 64% of cases, an anti‐adhesive solution was used on the face within 48 h of the onset of drainage. Sepsis evaluation was performed in 68% of cases. Rates of ear drainage peaked from 2008 to 2011 at 9.18 per 1000 admissions when a new anti‐adhesive product was used, declining to 0.66 post‐initiative (rate difference: −8.52; 95% CI: −12.00, −5.03). Conclusion Protecting the ear from anti‐adhesive solutions during tape removal may reduce rates of noninfectious ear drainage and limit unnecessary interventions.